Laminar Flow Protects Vascular Endothelial Tight Junctions and Barrier Function via Maintaining the Expression of Long Non-coding RNA MALAT1 - Yang, Fangfang; Zhang, Yunpeng; Zhu, Juanjuan; Wang, Jin; Jiang, Zhitong; Zhao, Chuanrong; Yang, Qianru; Huang, Yu; Yao, Weijuan; Pang, Wei; Han, Lili; Zhou, Jing (Frontiers in Bioengineering and Biotechnology, 2020)
Atherosclerotic plague plaque preferentially develops in arterial curvatures and branching regions, where endothelial cells constantly experience disturbed blood flow. By contrast, the straight arteries are generally protected from plague plaque formation due to exposure of endothelial cells to vaso-protective laminar blood flow. However, the role of flow patterns on endothelial barrier function remains largely unclear. This study aimed to investigate new mechanisms underlying the blood flow pattern-regulated endothelial integrity. Exposure of human endothelial cells to pulsatile shear (PS, (mimicking the laminar flow) compared to oscillatory shear (OS, (mimicking the disturbed flow) increased the expressions of long non-coding RNA MALAT and tight junction proteins ZO1 and Occludin. This increase was abolished by knocking down MALAT1 or Nesprin1 and 2. PS promoted the association between Nesprin1 and SUN2 at the nuclear envelopes, and induced a nuclear translocation of β-catenin, likely through enhancing the interaction between β-catenin and Nesprin1. In the in vivo study, mice were treated via intraperitoneal injection with β-catenin agonist SKL2001 or its inhibitor XAV939, and they were then subjected to Evans blue injection to assess aortic endothelial permeability. The aortas exhibited a reduced wall permeability to Evans blue in SKL2001-treated mice whereas an enhanced permeability in XAV939-treated mice. We concluded that PS laminar flow promotes nuclear localization of Nesprins, which facilitates the nuclear access of β-catenin to stimulate MALAT1 transcription, resulting in increased expressionss of ZO1 and Occludin to protect endothelial barrier function.